Fowl play - Pizzari, T (2007)
It is now well established knowledge that both males and females in most species are sexually promiscuous. When insemination is completed, a male is able to access and inseminate a female by means of interactions between competing ejaculates within the female reproductive tract. One good species to demonstrate this interaction is with red junglefowl chickens which live in south-east Asia. The male chickens that are dominant tend to guard a group of females and guard them from the advances of socially subordinate males. It was also found out that low quality sperm is more common than high-quality sperm. In addition, social switches are associated with the decrease in quality of sperm, especially for the dominant males. This finding suggests that the fowls can either be socially dominant, mate repeatedly with several hens and reduce the risk that his ejaculates will compete with the ejaculate of other males, or be subdominant, copulate less but inseminate more competitive ejaculates.